A Comparison between the Post-Operative Pain Relief in Total Hystrectomy with Epidural Bupivacaine and TAP Block - Sarosh Ul Hassan, Muhammad Amim Anwar, Syed Nouman Ahmed, Aqil Qayyum, Muhammad Arshed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anesthesia is essential in the treatment of postoperative pain. Epidural analgesia and trans versus abdominis plane (TAP) block are possible options for analgesia for abdominal surgery. Objective: The main objective of the study is to evaluate and compare the efficacy of epidural bupivacaine and trans versus abdominus plane (TAP) block to provide better post-operative pain relief in total abdominal hysterectomy. Study design and place of study: This study was a prospective randomized control trial conducted at Department of anesthesiology, Liaquat National Hospital, Karachi for the period July 2017- July, 2018. Methods: Total 101 patients were enrolled thorough pre anesthetic assessment before surgery and an informed and written consent was obtained. Patients were allocated in group A and B after taking all ASA monitoring, participants in group A had an epidural catheter passed while Group B patients were given transversus abdominis plane block intra-operatively. A Visual Analogue Scale (VAS) score was used to assess anxiety levels. Statistical test like the chi-square test was used, with a p-value of 0.05 being considered statistically significant Results: Total 101 participants enrolled, the average age was 45.48 ± 1.06 (Age Rang 30-60years). The mean age of patient in Epidural Group was 47.02± 7.62 as ccompared with TAP Block Group was 43.56± 13.35 with p-value 0.007. Majority of the patients has ASA II, 39(61.9%) and 24(38.1%) respectively with p-value 0.240. Pain score at 10 minutes in epidural and TAP Block was reported as 2.16±2.1o and 3.0±2.94 (mild pain) with p-value 0.000 while after 6 hours, the VAS pain score showed mild pain in epidural group as 1.96±1.67 but moderate to severe pain was observed in TAP block patients as 4.28±1.56 with insignificant p-value 0.162. Study findings will help care taker staff for Post-Operative Pain Relief after the surgery , the benefits of single shot TAP block could be of advantage in situations where epidural analgesia is contraindicated or not desired. Conclusion: The study concluded better pain relief in patients with epidural bupivacaine when compared with TAP block. Keywords: TAP Transversus Abdominus Plane ASA Physical Status Score VAS Visual Analogue Scale Epidural block, postoperative pain relief, Total Abdominal Hysterectomy, Transversus Abdominis Plane Block